THE IMPACT OF MULTICULTURAL-BASED CURRICULUM DEVELOPMENT IN INDONESIA: PHILOSOPHICAL AND PSYCHOLOGICAL FOUNDATIONS - Dea Marlinda Dea; Dila Septiani Dila; Elsa Nur Pareza Elsa; Keyla Nabela Larasati Keyla (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Lampung, 2026)
This study was motivated by the need to implement a multicultural-based curriculum in Indonesia, with the aim of understanding how philosophical and psychological foundations influence curriculum development. The primary objective of this study is to determine the extent to which the development of a multicultural-based curriculum has been implemented, as well as how philosophical and psychological foundations play a role in shaping students’ character to be tolerant and understanding of the cultural differences around them. The philosophical aspect is grounded in Pancasila, which prioritizes unity in diversity, serving as the primary foundation for this curriculum development. Meanwhile, the psychological aspectwhich takes into account students’ cognitive and emotional developmental stagesis also a key consideration, ensuring that learning materials related to multicultural education are well-received and understood in accordance with students’ ages and developmental levels. This study employs a literature review using a descriptive qualitative approach, involving the analysis of various books, journals, and other literature sources. The emphasis on the descriptive qualitative approach enables this study to provide a comprehensive overview of multicultural education concepts and their relevance within the context of Indonesian education. This study was conducted to answer the question of how philosophical and psychological foundations influence the development of a multicultural-based curriculum. The results of this study are expected to make a significant contribution to curriculum development so that it better meets the needs of a diverse society and fosters the creation of citizens who are tolerant and respectful of differences.